Limites entre educação e assistência: uma análise histórica e política da educação infantil no interior paulista - Minussi, Raquel Zanetti (2022)
Understanding the concept and conceptions of education and childhood in the contemporary world is essential in order to face the challenges imposed when thinking about quality education. In this work, the conceptions, practices and concepts that relate to early childhood education and welfare in the national and municipal scenario will be analyzed, having as the main reference the only daycare center in the municipality of São Sebastião da Grama, a small mountain town in the interior of São Paulo. In this context, in addition to the historical factors that we have covered in both spheres, we will analyze welfare actions, the foundation of the municipality, the origin of rural education, urbanization, philanthropy, the first daycare center under the responsibility of the public power, relating political, economic biases, social, cultural and pedagogical. These paths permeate and intersect with all these factors that sometimes intertwine and sometimes distance themselves from what we experience at the national and municipal levels. In this work, we seek to bring to light historical factors that are linked to public policies that determine the laws, regulations and references of early childhood education, initially in their philanthropic care linked to the work of parents and later to the daycare service guaranteeing the child’s rights. In this path, bibliographic references, primary documents and interviews were analyzed that shed light on the paths that education took in Brazil and especially in the municipality, presented in the context of childhood and the care of children of daycare age, since the foundation of the aforementioned municipality to the present day, reflecting on historical factors in the education of young children, public policies, legislation, regulations, investments, and how all these indicators influence and determine education and care for children in daycare centers.